(untitled) (Bangladesh Journal of Botany, 2024)
AM fungi have been widely studied in physiology and photosynthesis, but the drought tolerance of Xanthoceras sorbifolium by AM fungi has not been fully explored. In order to explore the drought stress and drought tolerance of X.sorbifolium seedlings inoculated with different AM fungi. We conducted an indoor pot experiment with four levels of drought stress on X.sorbifolium without inoculation with Funneliformis mosseae, Diversispora versiformis, Rhiaophagus intraradices and mixed fungi, respectively. The results showed the infection rate of each microbial agent can reach up to 88%. Under mild drought conditions, after 60 days of inoculation with Funneliformis mosseae,Diversispora versiformis, Rhiaophagus intraradices, and mixed microbes, the root surface area of X. sorbifolium seedlings increased by 47.63, 36.65, 10.35 and 54.42%, respectively, and the root volume increased by 59.97, 36.15, 58.83 and 60.72%. At different times and under different degrees of drought, inoculation with various microbial agents also resulted in varying degrees of improvement in biomass, root length, and other indicators, but had a weak effect on changing root configuration such as root tip and root bifurcation. Overall, the growth promoting effect of various microbial agents is the best under mild drought, with a microbial effect of mixed microbes>Diversispora versiformis>Funneliformis mosseae>Rhiaophagus intraradices. Bangladesh J. Bot. 53(4): 1055-1065, 2024 (December)